Social efficiency between mining and non-mining regions in Minas Gerais: an analysis using the malmquist index - Silva, Amanda Raphaela Silva e; Bueno, Alan; Ferraz, Diogo (Revista Gestão da Produção Operações e Sistemas, 2025)
Purpose: Compare the social efficiency indexes in the Minas Gerais state from 1990 to 2010. Methodology/Approach: This study uses a combination of parameters grouped by the method of data envelopment analysis (DEA) and by the Malmquist Index. Findings: We presented the top and bottom-ranked regions among the Minas Gerais municipalities. We analyzed these results by dividing them though regions with mining and no-mining regions. We found no relevant impacts, positive or negative, caused specifically by the mining activity on social efficiency. Research, practical & social implications: This article contributes to the formulation of public policies for human development in both mining and non-mining municipalities. Among the practical implications, the findings indicate the need for public policies aimed at improving the efficiency of financial resource allocation to promote human development. Regarding social implications, it is expected that the analysis of social efficiency will enhance the impact of other social programs (e.g., housing, health, and education) in the municipalities under study. Originality/ Value: There is a scarcity of studies analyzing social efficiency in mining and nonmining municipalities in developing countries, making this article a pioneer on the topic.